Homer's The odyssey - Ryken, Leland (Wheaton, Ill. : Crossway, 2013)
"We{u2019}ve all heard about the classics and assume they{u2019}re great. Some of us have even read them on our own. But for those of us who remain a bit intimidated or simply want to get more out of our reading, Crossway{u2019}s Christian Guides to the Classics are here to help. In these short guidebooks, popular professor, author, and literary expert Leland Ryken takes you through some of the greatest literature in history while answering your questions along the way. This guide opens up Homer{u2019}s The Odyssey and highlights the universal themes of endurance and longing for rest as displayed in this epic tale of a man trying to find his way home."--Publisher's description.
The Nature and Function of Literature -- Why the Classics Matter -- How to Read a Story -- The Odyssey: The Book at a Glance -- The Author and His Faith -- The Odyssey as Epic -- The Odyssey. What Went on in the House of Odysseus -- How the Council Met in the Market-Place of Ithaca, and What Came of It -- What Happened to Sandy Pylos -- What Happened in Lacedeimon [Sparta] -- Odysseus Leaves Calypso's Island -- How Odysseus Appealed to Nausicaa, and How She Brought Him to Her Father's House -- What Happened to Odysseus in the Palace of Alcinoos -- How They Held Games and Sports in Phaiacia -- How Odysseus Visited the Lotus-Eaters and the Cyclops -- The Island of the Winds; the Land of the Midnight Sun; Circe -- How Odysseus Visited the Kingdom of the Dead -- The Singing Sirens, the Terrors of Scylla and Charybdis, and the Cattle of Helios -- How Odysseus Came to Ithaca -- Odysseus and the Swineherd -- How Telemachos Sailed Back to Ithaca -- How Telemachos Met His Father -- How Odysseus Returned to His Own Home -- How Odysseus Fought the Sturdy Beggar -- How the Old Nurse Knew Her Master -- How God Sent Omens of the Wrath to Come -- The Contest with the Great Bow -- The Battle in the Hall -- How Odysseus Found His Wife Again -- How Odysseus Found His Old Father and How the Story Ended -- The Odyssey in Biblical Perspective -- Tie-Ins with the Book of Proverbs.
Includes bibliographical references (p. 76).
Keywords: Homer; Christianity and literature; Epic poetry, Greek -- History and criticism; Odysseus, -- King of Ithaca (Mythological character) -- In literature